Antimicrobial Properties and Cytotoxicity of an Antimicrobial Monomer for Application in Prosthodontics - Regis, Romulo Rocha; Della Vecchia, Maria Paula; Pizzolitto, Antonio Carlos [UNESP]; Compagnoni, Marco Antonio [UNESP]; Chaves Souza, Pedro Paulo [UNESP]; de Souza, Raphael Freitas (Wiley-Blackwell, 2012)
Purpose: This study aimed to investigate the antimicrobial properties and cytotoxicity of the monomer methacryloyloxyundecylpyridinium bromide (MUPB), an antiseptic agent capable of copolymerizing with denture base acrylic resins. Materials and Methods: The antimicrobial activity of MUPB was tested against the species Candida albicans, Candida dubliniensis, Candida glabrata, Lactobacillus casei, Staphylococcus aureus, and Streptococcus mutans. The minimum inhibitory and fungicidal/bactericidal concentrations (MIC, MFC/MBC) of MUPB were determined by serial dilutions in comparison with cetylpyridinium chloride (CPC). The cytotoxic effects of MUPB at concentrations ranging from 0.01 to 1 g/L were assessed by MTT test on L929 cells and compared with methyl methacrylate (MMA). The antimicrobial activity of copolymerized MUPB was tested by means of acrylic resin specimens containing three concentrations of the monomer (0, 0.3, 0.6% w/w). Activity was quantified by means of a disc diffusion test and a quantification of adhered planktonic cells. Statistical analysis employed the Mann-Whitney test for MIC and MFC/MBC, and ANOVA for the microbial adherence test (a= 0.05). Results: MUBP presented lower MIC values when compared with CPC, although differences were significant for C. dubliniensis and S. mutans only (p= 0.046 and 0.043, respectively). MFC/MBC values were similar for all species except C. albicans; in that case, MUPB presented significantly higher values (p= 0.046). MUPB presented higher cytotoxicity than MMA for all tested concentrations (p < 0.001) except at 0.01 g/L. Irrespective of the concentration incorporated and species, there was no inhibition halo around the specimens. The incorporation of MUPB influenced the adhesion of C. albicans only (p= 0.003), with lower CFU counts for the 0.6% group. Conclusions: It was concluded that non-polymerized MUPB has an antimicrobial capacity close to that of CPC and high cytotoxicity when compared with MMA. The antimicrobial activity of MUPB after incorporation within a denture base acrylic resin did not depend on its elution, but was shown to be restricted to C. albicans.
Keywords: Local anti-infectious agents; denture bases; quaternary ammonium compounds; stomatitis under dentures; acrylic resins